Correlation between Hashimoto’s thyroiditis and polycystic ovary syndrome: A systematic review and meta-analysis - Hu, Xiaojie; Chen, Yuquan; Shen, Yiting; Zhou, Siyuan; Fei, Wenting; Yang, Yuxin; Que, Huafa (Frontiers in Endocrinology, 2022)
Objective A growing body of research suggests that patients with polycystic ovary syndrome (PCOS) may be at increased risk of developing Hashimoto’s thyroiditis (HT), and having both conditions can make the condition worse. However, current research views are not uniform. Therefore, to explore the link between PCOS and HT, we conducted this study. Methods From the establishment of the database to August 2022, we searched 2 databases to study the correlation between Hashimoto’s and polycystic ovary syndrome. Two authors independently screened the articles for eligibility, and three authors extracted relevant data. Statistical analysis was performed using STATA16.0 software. Results A total of 20 studies were included, including 7 case-control studies and 13 cross-sectional studies. A total of 13 countries and 7857 participants were embraced. Studies have demonstrated that both PCOS patients have an increased risk of HT, and meanwhile, HT patients also have an increased risk of PCOS compared with controls. The study also incorporated that the prevalence of HT in PCOS patients in India and Turkey was higher than in other countries, and the prevalence of HT in PCOS patients in South America was higher than in Asia and Europe. Conclusions In conclusion, our study illustrates that there is a correlation between PCOS and HT, and it is necessary to further study the underlying mechanism between PCOS and HT. At the same time, it is of great significance to regularly screen PCOS patients for HT risk and HT patients for PCOS risk. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier CRD 42022351168.